Ultra-stable and bifunctional free-standing SiC photoelectrocatalyst for water remediation. (10th April 2023) - Liu, Shuang; Yang, Tao; Wang, Enhui; Wang, Hailong; Du, Zhentao; Cao, Sheng; Zhang, Qiaobao; Chou, Kuo-Chih; Hou, Xinmei
Abstract: Nowadays, the development of stable and bifunctional photoelectrocatalyst to simultaneously remove heavy metal ions and organic pollutants in wastewater is still challenging. In this work, an integrated N doped 4H–SiC photoelectrocatalyst with a 3D nanohole structure is constructed by the anodic oxidation process. The obtained N doped 4H–SiC nanohole arrays (N–4H–SiC NHAs) exhibit satisfactory hexavalent chromium (Cr(VI)) reduction (94.9%), removal of tetracycline (TC, 87.1%) and rhodamine B (RhB, 83.4%) within 120 min. The removal efficiencies of Cr(VI) and TC remain 93.0% and 72.2% after ten cycles of degradation tests, indicating the good reusability of N–4H–SiC NHAs. The effects of pH value, common inorganic ions and temperature on PEC performance are investigated. Furthermore, it is proved that Cr(VI) is transformed into Cr(III) through a three-electron transfer process by electron paramagnetic resonance technique and the degradation pathways of TC are proposed by high-performance liquid chromatography-mass spectrometry. The superior PEC activity is mainly attributed to the narrower band gap caused by N doping and the highly oriented nanohole arrays, which can enhance the absorption of visible light, promote the separation and transportation of photocarriers, provide highly exposed surface area and abundant active sites for redox reactions. This research provides promising prospects for the design and synthesis of stable and bifunctional photoelectrocatalyst in water remediation. Graphical abstract: Image 1 Highlights: The N–4H–SiC NHAs can be used for reduction of heavy metal ions and degradation of organic pollutants. The obtained N–4H–SiC NHAs exhibit superior reusability and durability. Photoelectrocatalytic mechanism under N–4H–SiC NHAs electrode is deduced.